PENGARUH TEKANAN AIR DAN SUDUT NOZZLE TERHADAP KARAKTERISTIK OUTPUT PADA PROTOTYPE PLTMH DENGAN TURBIN PELTON - I Made Ardika Tommy Saputra; Lie Jasa; I Wayan Arta Wijaya (Jurnal SPEKTRUM, 2020)
Pelton turbine is an impulse turbine that is different from other turbines where the peltonturbine utilizes a large high water fall (head), even with a small water discharge. The problemwith Pelton turbine is that the head is still difficult to control because this type of turbine uses ahigh head to rotate the turbine runner and there is no formula / equation to determine the angleof the nozzle which produces maximum output. Based on the problems described, it isnecessary to make a micro hidro power plant prototype using a pelton turbine with a laboratoryscale so that it can do the testing of the influence of water and the nozzle angle to obtainmaximum output results on a micro hidro power plant using a pelton turbine. The prototypetesting in this study used various water pressures, namely 5 psi, 9 psi, 13 psi, 17 psi, 21 psi,and 25 psi with nozzle angles, namely 60º, 75º, and 90º. Based on the results of the study, anincrease in the value of water pressure provided with an optimal nozzle angle will cause themicro hidro power plant performance to increase. The maximum output obtained is when thewater pressure is 25 psi with a nozzle angle of 90º which produces a turbine rotation of 917 rpmbefore the generator is coupled and 326 rpm after the generator is coupled, the generatorrotation is 1321 rpm, the generator voltage is 12.9 Volts, generator power is 30.96 Watt, torque is 0.98 Nm, and the highest efficiency occurs when the water pressure is 21 psi with a nozzleangle of 90º which is 3.91%.